THE EFFECT OF ADMINISTRATION OF BREASTFEEDING MEDICATIONS AT 36-40 WEEKS OF PREGNANCY FOR IMPROVING ASI AFTER BIRTH AT PMB BD ELIN YULIANENGSIH., S.Si.T - Munna, Siti Lailul; Yuningsih, Sukarni Setya (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
Background: Mother's milk (ASI) is the best natural nutrition for babies with the most appropriate nutritional content for optimal growth. Currently, there are still many mothers who do not breastfeed their babies. This is influenced by various factors, including breast milk not coming out immediately after giving birth or not producing breast milk (ASI). The reality in the field shows that low breast milk production in the first days after giving birth is an obstacle in providing breast milk early. In efforts to express breast milk (ASI), there are 2 things that influence it, namely production and expenditure. The production of breast milk (ASI) is influenced by the hormone prolactin, while production is influenced by the hormone oxytocin. The decrease in the production and release of breast milk (ASI) in the first days after giving birth can be caused by a lack of stimulation of the hormones prolactin and oxytocin which play an important role in smooth production and expenditure of breast milk (ASI). Several factors influence the flow and flow of breast milk (ASI), namely breast care, frequency of breastfeeding, parity, stress, illness or maternal health, consumption of cigarettes or alcohol, contraceptive pills, nutritional intake. Research Objective: To determine the effect of giving breast milk-stimulating drugs at 36-40 weeks of pregnancy for smooth breastfeeding after giving birth at PMB Bd. Elin Yulianengsih., S.Si.T. Research Method: The research design uses the One Group Pretest-Posttest form, namely a design that is observed twice, namely before and after being given breast milk-stimulating medication. Research Results: Based on the Paired T Test, it was found that Asymp Sig (2-tailed) was 0.000 < 0.05, meaning that Ho was rejected and H1 was accepted, so it can be said that there is a significant influence between the administration of breast milk-stimulating drugs on breast milk production in breastfeeding mothers at PMB Bd. Elin Yulianengsih. Conclusion: There is an influence between the administration of breast milk-stimulating drugs on breast milk production in mothers after giving birth at PMB Bd. Elin Yulianengsih.